2004
DOI: 10.1143/jjap.43.5425
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Frequency Modulation Twisted Nematic LCDs Doped with Palladium (Pd) Nanoparticles

Abstract: Twisted nematic liquid crystal display (TN-LCD) devices, composed of nematic liquid crystal (NLC), doped with palladium (Pd) nanoparticles, which are protected with the same NLC molecules of 5CB (Merck, K-15), show electrooptic characteristics that are featured by a frequency modulation and fast response. This device is called FM-TN-LCD. In this paper, we report that the frequency range in the FM-TN-LCD spreading from tens Hz to an upper limit 1 kHz, depending on the concentration of nanoparticles, correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Liquid crystal displays (LCDs) doped with metal NPs such as silver (Ag), gold (Au), palladium (Pd), platinum (Pt), or their alloys exhibited faster response times [8][9][10][11][12] than those of LCDs with conventional driving methods.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystal displays (LCDs) doped with metal NPs such as silver (Ag), gold (Au), palladium (Pd), platinum (Pt), or their alloys exhibited faster response times [8][9][10][11][12] than those of LCDs with conventional driving methods.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work was to research the possibilities for manifestation of the structural ordering of С60D molecules in NLC and to define what methods serving as a basis of the changes in NLC properties can be investigated most efficiently [5,6].…”
Section: Semiconductor Physics Quantum Electronics and Optoelectronicsmentioning
confidence: 99%
“…The modification of physical properties of liquid crystals by doping nanomaterials has received much attention from the view point of the enhancement of the performance of LCDs. Reflecting these trends several research groups reported on heterogeneous liquid crystal suspensions using; ferroelectric nanoparticles [1], ferromagnetic particles [2], fullerene [3], carbon nanotubes [4], diamond powders [5], metal nanoparticles [6,7], and metal nanorods [8]. In particular, strong activities have been reported for barium titanate (BaTiO 3 ) nanoparticles doped in nematic liquid crystalline mixtures [9].…”
Section: Introductionmentioning
confidence: 99%